2004
DOI: 10.1177/1541204004267780
|View full text |Cite
|
Sign up to set email alerts
|

The Code of the Street

Abstract: Based on extensive field research, Elijah Anderson argues that the behavior of many youths is influenced by a street culture or "code" that prescribes violent reactions to interpersonal attacks and shows of disrespect. Although Anderson's account has been well received by the criminological community, questions remain about the validity and generality of his findings. To address these issues, the authors review other (mostly quantitative) studies of youth violence and consider whether the findings of these stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Scholars have suggested that individuals in disadvantaged contexts may rely on a unique set of cognitive scripts to guide their behavior in social interactions (Luckenbill and Doyle 1989;Wilkinson and Fagan 1996;see also McGloin et al 2011), including a heightened proclivity for aggression. Neighborhood norms have been examined in relation to individual-level behaviors (e.g., Anderson 1999;Brezina et al 2004;Stewart and Simons 2010), and research findings are generally supportive of the notion that the neighborhood culture is a significant predictor of violence.…”
Section: Community Norms and Violencementioning
confidence: 96%
“…Scholars have suggested that individuals in disadvantaged contexts may rely on a unique set of cognitive scripts to guide their behavior in social interactions (Luckenbill and Doyle 1989;Wilkinson and Fagan 1996;see also McGloin et al 2011), including a heightened proclivity for aggression. Neighborhood norms have been examined in relation to individual-level behaviors (e.g., Anderson 1999;Brezina et al 2004;Stewart and Simons 2010), and research findings are generally supportive of the notion that the neighborhood culture is a significant predictor of violence.…”
Section: Community Norms and Violencementioning
confidence: 96%
“…Strains that are highly central to individuals increase their likelihood of delinquent coping (Liu ), which is illustrated by the strength of the association between the receipt of interpersonal injustice or disrespect and criminal behavior (e.g. Anderson ; Brezina et al ; Griffiths et al ; Van Yperen et al ). Kennedy et al () found that interpersonal injustice is a stronger predictor of workplace aggression than a comparative amount of distributive injustice.…”
Section: Strain Injustice and Crimementioning
confidence: 99%
“…Research on the association between respect and the need to maintain one's masculinity (Kupers ; Messerschmidt ) suggests that crime would be more likely in response to strains that insult, degrade, or strip individuals of their status (Anderson ; Brezina et al ; Griffiths et al ). These strains, moreover, should be perceived as being especially high in magnitude by individuals who are disadvantaged, as they do not have a high degree of status to begin with (Anderson ; Brezina et al ).…”
Section: Conditioning Factorsmentioning
confidence: 99%
“…6 Characteristics and patterns of gang violence have been extensively studied in within both criminology and sociology (Brezina, Agnew, Cullen, and Wright 2004;Jimerson and Oware 2006;Matsueda, Drakulich, and Kubrin 2006;Stewart, Schreck, and Simons 2006;Taylor, Esbensen, Brick, and Freng 2010).…”
Section: Notesmentioning
confidence: 99%